Array comparative genomic hybridization analysis of products of conception in recurrent pregnancy loss for specific anomalies detected by USG - Kinjal Gajjar; Alpesh Patel; B I Patel; Shiva Chettiar; Devendrasinh Jhala (Bioscientifica, 2023)
To evaluate the proportion of chromosomal abnormalities in recurrent pregnancy loss (RPL) assisted by array comparative genomic hybridization (aCGH) bright out with higher detection rate, more accuracy, and less sample failure as compared with conventional cytogenetic analysis. In this study, product of conception samples with abnormal ultrasonogram (USG) findings of the fetus and clinical history of RPL were first processed for karyotyping and fluorescence in situ hybridization (FISH) analysis. Normal results given by karyotype and FISH samples with major anomalies detected by ultrasound with RPL were divided into six groups and aCGH was performed to detect the gain or loss and copy number variations (CNVs) of a particular gene present in chromosomal segments. Among a total of 300 products of conception samples, 100 abnormal samples were identified either by karyotype (n = 70) or by FISH (n = 30). From the remaining 200 samples, 5 showed the presence of maternal cell contamination excluded. aCGH analysis revealed (n = 195) that 74 (38%) samples with CNVs and 2 samples with variants of unknown clinical significance were clinically associated with the clinical findings and 121(62%) samples showed no change in CNVs. The most frequent CNVs were loss of chromosome regions at 2q33.1, 7q11.21, 15q11.1, 16p11.2, Xp22.33, and Yp11.32. CNVs at arr[GRCh37]7p22.3,p21.2(830852-15124702)×1,7q34q36.3(141464180-158909738)×3, 14.2 Mbp deletion of 7p22.3p21.2 (SUN1 gene) and 17.4 Mbp duplication of 7q34q36.3 (KCNH2, CNTNAP2, and SHH genes) were found in one sample, and CNVs at arr[GRCh37]8p22.2q22.3(86326349-105509986)×1 and 2.48 Mbp deletion of 8p22.2q22.3 (GRHL1 gene) were found in another sample.